07.17 The mutated rna splicing protein hnrnp-a3 is a novel autoantigen in systemic rheumatic diseases a link to warburg effect in ra. (1st March 2017) - Marklein, Bianca; Adolph, Kerstin; Krenn, Veit; Steiner, Günter; Hansson, Monika; Rönnelid, Johan; Burmester, Gerd R; Skriner, Karl
Abstract : Objective: Novel mutated hnRNP-A3 (MA3)was cloned out of RA synovial tissue involved in alternative splicing of PK2 linking it directly to Warburg effect and lactate production in RA. Methods: After immunoblotting and 2D-gel-eletrophoresis out of a semipurified hnRNP fraction two protein spots were sequenced and identified to be highly similar to hnRN-A3. hnRNP-A3 variants were cloned from RA synovial-tissue. 3700 RA sera were screened for the presence of mutated anti-hnRNP-A3 autoantibodies using recombinant proteins and mutated citrullinated A3 peptides (MCA3) thereof. Identification of RNA and antibody binding sites to hnRNP A3 (MA3). Expression of hnRNP-A3 in synovial tissue was analysed by immunohistochemistry. Results: Autoantibodies to MA3 protein were detected in 13% of RA (n=215) patients, in 9% SLE(n=154), in 27% of MCTD patients (n=44/10) and in less than 5% of 129 patients with other rheumatic disorders but not at all in healthy controls on immunoblot. When using native MA3-ELISA 22% of early RA patients (n=130) were detected and 87% of these patients had erosive arthritis. Identical modification on MA3 as in cancer cells were identified in synovial tissue and verified by MS and DNA sequencing. Using 2–3 citrullinated MCA3 peptides up to 81% of patients (n=150) with established and 67% (n=2926) of patients with an early RA with a specificity of 97% were detected. In early RA 27% and 25% in established RA of CCP2 negative and 93% of CCP2 positive patients were identified. By combining with the already established CCP2 and the new MCA3, 72% of early patients are positive. MCA3 autoantibodies predominantly occur (p<0.001) in an erosive, severe course of disease. MRL Lpr/lpr sera were hnRNP-A3 reactive and the antibody generation is Toll 7 and 9 dependent. Anti-hnRNP-A3-antibodies are directed to conformational RNA binding epitopes. Expression of hnRNP-A3 revealed the antigen is overexpressed in RA synovial tissue. Conclusion: Mutated hnRNP-A3 is as a novel Toll7/9 dependent autoantigen in systemic rheumatic diseases. These mutated proteins are components of RNA and DNA containing alternative splicing complexes leading to the Warburg effect and predominantly occurring in an erosive and severe courses of RA.